A platform for enterprise-wide healthcare knowledge management - Yu-N, Cheah; Yong, Han Chong; Manickam, Selvakumar (2004)
The importance of effective information and knowledge management in enterprises has spurred the development of numerous information and knowledge management software.Whilst emphasis is placed on effective document management, the essence of knowledge management is diluted as the focus is presently on managing uninterpreted data and information in document-type formats.To address this issue of the lack of true knowledge management in enterprises, especially in healthcare enterprises, we propose a Platform for Enterprise-Wide Healthcare Knowledge Management (KM-Platform).This platform is made up of two suites of applications and services, i.e. the Intelligent Agent-Based Knowledge Management Application Suite and the Strategic Visualisation, Planning and Coalition Formation Service Suite.